New organic semiconductor materials - Yakuphanoğlu, Fahrettin; Soykan, Cengiz; Coskun, Rarnazan (Wiley, 2008)
BACKGROUND: Electrical conductivity, photoconductivity, voltage-controlled negative resistance and thermal properties of copolymers of 2-acrylamido-2-methyl-1-propanesulfonic acid and maleic acid were investigated in order to obtain new organic semiconductors. RESULTS: The room temperature conductivity of three different copolymers was found to be in the range 1.28 x 10(-8) - 1.20 x 10(-7) S cm(-1). The dark- and photo-current-voltage characteristics indicate that the copolymers exhibit voltage-controlled differential negative resistance behaviour. The electrical conductivity of the polymers increases by photo-illumination, suggesting that the polymers exhibit photoconductivity. The width of the exponential tail in the forbidden band gap of the three polymers was determined via the transient photocurrent technique and E-0 values were in the range 34.4-36.49 meV. CONCLUSION: The results suggest that the copolymers could be used as organic semiconductor materials. (C) 2007 Society of Chemical Industry.
Keywords: organic semiconductor; polymers; VCNR device; photoconductivity